PENGARUH DOLOMIT TERHADAP NITROGEN DAN pH PUPUK ORGANIK CAIR URIN DOMBA LOKAL - Zaenal Nur Riyadi; Nunur Nuraeni; Aqil Adyatama (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2026)
Sheep are a significant contributor of organic waste. Dolomite has the ability to neutralize acidity. The addition of dolomite to sheep urine is thought to lower the pH, while increasing the nutrient content in the resulting POC. The purpose of the research carried out was to analyze the effect of dolomite addition on pH, determine the effect of dolomite addition on nutrient content (Nitrogen) and determine the optimal dose of dolomite addition that produces the best pH and nutrient content in sheep urine POC. The research was conducted in Klegenrejo Village, Klirong District, Kebumen Regency. The research will be carried out in December 2025. The research was carried out using a completely randomized design (CRD) with 4 treatments and 3 replications, namely P0 (without dolomite addition), P1 (Addition of 1% dolomite per liter of sheep urine), P2 (Addition of 3% dolomite per liter of sheep urine) and P3 (Addition of 6% dolomite per liter of sheep urine). The data obtained will be subjected to Descriptive Test, Normality Test, T Test between treatments (one way ANNOVA). The results of the study showed that the addition of dolomite to sheep urine POC had no significant effect on pH levels and nitrogen nutrients in each treatment given with a significance value (P>0.05), but treatment P3 (addition of 6% dolomite) was the most optimal administration with a pH of 7.55 and a nitrogen nutrient content of 0.110%. Keywords: Dolomite, Liquid Organic Fertilizer, Sheep, pH, Nutrients